Analysis of China’s carbon financial Development’s impact on reducing emissions using the BCC and Malmquist models - Chunzhe, Li; Xueyuan, Ding; Tao, Meng; Libo, Xu; Haibo, Fu; Gang, Liu; Sihang, Pan; Jiarong, Liu; Zeqi, Ge (Frontiers in Energy Research, 2024)
This study aims to explore the impact of the development of carbon finance in China on the effect of carbon emission reduction and analyze its role in promoting the development of low-carbon economies. We chose five representative provinces (autonomous regions) in China to study the carbon financial markets. We did this by making an evaluation index system and using systematic cluster analysis (SCA) and data envelopment analysis (DEA) methods. Using the DEA-BCC model and DEA-Malmquist index, the carbon emission reduction effect between 2022 and 2023 was analyzed in depth. The analysis results show that China's carbon finance development has a significant positive impact on carbon emissions reduction, but there are significant differences in the effects between different regions. Specifically, Beijing and Guangdong achieved DEA efficiency effectiveness during the study period, while the DEA efficiency values of Jilin Province, Ningxia Hui Autonomous Region, and Xinjiang Uygur Autonomous Region are less than 1, indicating that these regions have efficiency losses in carbon emission reduction and need to further optimize their input-output structure. This study not only reveals the problems and room for improvement in China's carbon finance development, but also provides a scientific basis for the formulation of relevant policies. Finally, the article puts forward a series of policy recommendations, including improving the market mechanism, promoting technological innovation, and increasing social participation, so as to promote the healthy development of China's carbon financial market and help achieve the country's carbon peak and carbon neutrality goals.